2003
DOI: 10.1071/ea02233
|View full text |Cite
|
Sign up to set email alerts
|

The response of canola (Brassica napus L.) to tillage and fertiliser placement in contrasting environments in southern NSW

Abstract: Land preparation for canola (oilseed rape; Brassica napus L.) by conventional cultivation can involve a number of workings, resulting in soil degradation and reduced crop growth. Minimum-tillage systems may help overcome these problems, but the placement of fertiliser at sowing must avoid chemical injury to germinating seed. The responses of canola cultivars to tillage and fertiliser placement were studied for 2 seasons at high (Breakfast Creek, 1997; Harden, 1998) and low (Ardlethan, 1997–98) rainfall sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…The progressive increase in number of fruits per plant, fruit weight and fruit yield (t ha -1 ) might be due to the optimum dose of NPK, which accelerated mobility of photosynthesis from the source to the sink as influenced by the growth hormone, and NPK uptake. These finding are in agreement with the findings of Umamhaswrappah (2004) in Bottle gourd, Cheema et al, (2001) and Hocking et al, (2003) in canola, Jillani et al, (2009 and Prabhu et al, (2003) in cucumber. Total Soluble Solids (5.50 o Brix), in fruit was significantly improved by the application of inorganic fertilizer @ 100 per cent.…”
Section: Resultssupporting
confidence: 83%
“…The progressive increase in number of fruits per plant, fruit weight and fruit yield (t ha -1 ) might be due to the optimum dose of NPK, which accelerated mobility of photosynthesis from the source to the sink as influenced by the growth hormone, and NPK uptake. These finding are in agreement with the findings of Umamhaswrappah (2004) in Bottle gourd, Cheema et al, (2001) and Hocking et al, (2003) in canola, Jillani et al, (2009 and Prabhu et al, (2003) in cucumber. Total Soluble Solids (5.50 o Brix), in fruit was significantly improved by the application of inorganic fertilizer @ 100 per cent.…”
Section: Resultssupporting
confidence: 83%
“…The study of Cheema et al, (2001) found that the number and weight of fruits increase because of adding of nitrogen and phosphorus one by one. The superior growth of crop because of nitrogen fertilizer observed by Hocking et al, (2003).…”
Section: Resultsmentioning
confidence: 99%
“…2). This is because seed-row placement improves the accessibility of P during early seedling development (Grant and Bailey, 1993), and the canola biomass can compensate for low plant stands (Hocking et al, 2003). A reduction in the early-season DMY of >30% is required to significantly reduce the canola seed yield (Bélanger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%